2023
DOI: 10.3390/buildings13112890
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Critical Project Success Factors—Sustainable Management of the Fast-Track Construction Industry

Khalid K. Naji,
Murat Gunduz,
Mohamed Adalbi

Abstract: Fast-track construction has recently become the prevailing construction approach globally. It enables owners and developers to make rapid returns on investment through shortened construction periods. This strategy has many effects on the industry; therefore, four groups of factors were studied in this project: (1) financial, (2) logistics and finance, (3) management, and (4) legal. A 22-question survey was distributed to 155 professionals in the construction industry, who evaluated the impact of the stated fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…More recently, a study conducted by Ahmad [19] revealed factors with critical significance in green building projects, which included the proficiency of the project clients, project team collaboration, the early engagement of the project team, the client's motivation to achieve sustainable outcomes, and rigor in project design development. Naji et al [20] examined the critical success factors of fast-track construction projects. Their statistical analysis revealed the most significant factors that impacted fast-track project performance, including poor communication among the design and construction teams, large amounts of rework, low-quality work performed by the contractor, design errors, insufficient payment according to the terms agreed with the client, and the unavailability of materials.…”
Section: Critical Success Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, a study conducted by Ahmad [19] revealed factors with critical significance in green building projects, which included the proficiency of the project clients, project team collaboration, the early engagement of the project team, the client's motivation to achieve sustainable outcomes, and rigor in project design development. Naji et al [20] examined the critical success factors of fast-track construction projects. Their statistical analysis revealed the most significant factors that impacted fast-track project performance, including poor communication among the design and construction teams, large amounts of rework, low-quality work performed by the contractor, design errors, insufficient payment according to the terms agreed with the client, and the unavailability of materials.…”
Section: Critical Success Factorsmentioning
confidence: 99%
“…Initially, a total of 225 individual factors reported in relevant previous studies were investigated. To correspond with the characteristics of the Thai construction industry, a total of 179 factors were explored [2][3][4][7][8][9][10][11][12][13][14][15][16][17][18][19][20]22,23,29,30,. Among these, 99 factors were selected, 47 modified, and 30 merged, with 3 new factors added.…”
Section: Identification Of Research Variablesmentioning
confidence: 99%